Dampak Ketakutan terhadap Proses Intranatal - Lestari, Selvia; Hermayanti, Yanti; Maryati, Ida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the impact of fear on intranatal and postnatal processes. The research method used was a scoping review of articles about the effects of fear of giving birth by searching database sources from Pubmed, Ebsco, and the Google Scholar search engine. The keywords used for the first search are